Long-Term Effects of CIPS-based Training Module on Professional Elementary School Teachers - Erni Munastiwi (Jurnal Pendidikan Indonesia, 2021)
CIPS-based Training Module has been developed to encourage teachers to improve their personal skills. Hence, the aim of this study is to investigate the long-term effects of the CIPS-based Training Module on the elementary school teachers. This study used the quasi-experimental design that involved 63 elementary school teachers. The teachers were divided into the experimental and control groups to test the objective of this study. The indicators of data analysis used in this study are mean score, standard deviation and independent sample t-test. The results show that there is a significant difference between the experimental and control groups. The experimental group obtained a higher mean score than the control group, which indicates that the CIPS-based Training Module has a positive long-term effect on the elementary school teachers from the experimental group. Hence, it is recommended the CIPS-based Training Module be implemented in the training of teachers, as their thinking and teaching skills will improve, which in turn will benefit the students in attaining high achievement.